Trans-Cinnamaldehyde Attenuates Enterococcus faecalis Virulence and Inhibits Biofilm Formation - Islam A. A. Ali; Jukka P. Matinlinna; Celine M. Lévesque; Prasanna Neelakantan (MDPI AG, 2021)
Enterococcus faecalis as an important nosocomial pathogen is critically implicated in the pathogenesis of endocarditis, urinary tract, and persistent root canal infections. Its major virulence attributes (biofilm formation, production of proteases, and hemolytic toxins) enable it to cause extensive host tissue damage. With the alarming increase in enterococcal resistance to antibiotics, novel therapeutics are required to inhibit E. faecalis biofilm formation and virulence. Trans-cinnamaldehyde (TC), the main phytochemical in cinnamon essential oils, has demonstrated promising activity against a wide range of pathogens. Here, we comprehensively investigated the effect of TC on planktonic growth, biofilm formation, proteolytic and hemolytic activities, as well as gene regulation in E. faecalis. Our findings revealed that sub-inhibitory concentrations of TC reduced biofilm formation, biofilm exopolysaccharides, as well as its proteolytic and hemolytic activities. Mechanistic studies revealed significant downregulation of the quorum sensing fsr locus and downstream gelE, which are major virulence regulators in E. faecalis. Taken together, our study highlights the potential of TC to inhibit E. faecalis biofilm formation and its virulence.